Photons Motion in Charged Anti-De Sitter Black Holes - Cruz-Marin, N (2013)
In this work we study the null geodesics in the background of Reissner-Nordström Anti de Sitter black hole. We compute the exact trajectories in terms of Weierstrass elliptic functions, obtaining a detailed description of the orbits in terms of the charge, mass and the cosmological constant. The trajectories of the photon are classified using the impact parameter. © 2012 Springer Science+Business Media Dordrecht.